Diagenetic history of the lower oligocene algal limestone member of the Al Bayda For-mation, at Al Wattayatt area, Al Jabal Al Akhdar, NE Libya. - El-Shawaihdi, Moftah; Saleh, Aiman (Libyan Journal of Science &Technology, 2022)
The Algal Limestone Member of the Al Bayda Formation has been studied along Deryanah-Al Abyar road cut at Al Wattayatt area, Al Jabal Al Akhdar. The member was subdivided into five lithofacies based on petrographic examination; from bottom to top are; wackestone lithofacies, boundstone lithofacies, grainstone lithofacies, mudstone-wackestone lithofacies, and packstone lithofacies. Limestone is the dominant lithology with coralline red calcareous algal, nummulites, bryozoans, echinoids, and few corals are also present. Lithological description and paleontologic content indicate that this member was likely deposited within a shallow marine or near-surface environment that was dominated during the Lower Oligocene. However, diagenetic analysis reveals two stages of paragenetic processes, which had a great effect on the development of the depositional environment and the diagenetic history of this member. The early-stage includes grain dissolution, brittle fracture, pyrite formation, and early cement. The late-stage includes secondary cement, neomorphism (recrystallization), and dolomitization.